Problems of the Quran Learning Process During the Covid-19 Pandemic - Azizah, Ratna; M, Iswantir; Guslianto, Guslianto (STIT Ahlussunnah Bukittinggi, 2022)
The author's background in conducting this research is because there is a phenomenon that has occurred since the COVID-19 pandemic in the Quran Education teacher strategies have not varied in preparing learning to read the Quran since the covid-19 pandemic, there have been many mistakes made by students in applying tajwid knowledge when reading the Quran, and there have been obstacles in the learning process during covid-19 resulting in learning dynamics both on the part of teachers and students. This research aims to determine the implementation of learning strategies to read the Quran since the COVID-19 pandemic and to find out the obstacles to implementing learning strategies to read the Quran since the COVID-19 pandemic. This type of research uses field research, which is a form of research intended to describe phenomena. Phenomena that exist in the field, whether natural phenomena or human engineering. The object of this research is the implementation of teacher strategies in learning to read the koran since the COVID-19 pandemic. Data collection techniques include interviews, observation, and documentation. The obstacle from parents is that they don't agree with online learning because they don't have the money to buy a package and the network is often lost.